Teaching Soft OR/MS Methodologies: What, Why and How - Ackermann, Fran (2015)
This article explores the value of soft OR methods through the device of Kipling's 6 wise men reflecting on what is soft OR, why teach it, who and when should it be taught, and finally how should it be taught. This article notes the evolution and coming of age of the methodologies before moving to the what, why, and how elements, and concludes with some suggestions for future development. This article aims to also provide a good overview of the field of soft OR with a wide range of reference material so those interested in the field and/or particular aspects are able to explore in more depth.